Factors associated with knowledge on gastritis among undergraduates of Faculty of Allied Health Sciences, University of Jaffna - Atapattu, A.M.P.R.; Jayasooriya, R.L.A.S.; Jegapragash, V.; Vathulan, S. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka., 2023)
Introduction: Gastritis is a common inflammatory disease condition. The most common cause is Helicobacter pylori infection. It can be affected the quality of life as well as end-up with life threading conditions such as gastric cancer. Undergraduates of Faculty of allied health sciences are the future health professional and they should have adequate knowledge on it to educate the community. Objective: To assess the knowledge on gastritis and the associated factors on it among undergraduates of Faculty of Allied Health Sciences University of Jaffna. Methodology: This was descriptive cross-sectional study done among the nursing, pharmacy and medical laboratory sciences undergraduates of Faculty of Allied Health Sciences University of Jaffna. Study population was 649 and stratified random sampling method was used to find the sample of 426. Data collection was done by using the pretested self-administered questionnaire. Data were analyzed by using SPSS 25 (Statistical Package of Social Science) and descriptive statistics was used to describe the variables, and chi squared test was used to find the association. Results: Out of 426 participants 388 participants had responded (response rate: 91.07%). Within those 67.5% participants were female and 27.8% participants were studying nursing, 35.6% were studying pharmacy and 36.6% were studying medical laboratory sciences. According to the results 43% participants had been diagnosed with gastritis. In the findings 12.4% had adequate knowledge, 54.6% had moderately adequate knowledge and 33% had inadequate knowledge about gastritis. Mean of the knowledge was 59.41 with the range from 15 to 100. The knowledge on gastritis had significantly associated with age (p=0.000), nationality (p=0.027), Religion (p=0.017), and academic year (p=0.000). Conclusion: Knowledge on gastritis of the undergraduates were moderately adequate level. Knowledge on transmission of Helicobacter pylori with faecal contamination, diagnostic test of gastritis and medical nutrition therapy had been noticed in low level.
Keywords: Gastritis; Knowledge; Undergraduates